PrQS firms’ perspectives impacting on the employability of quantity surveying graduates - Tiyiso Mavasa; Rolien Terblanche (Journal of Construction Project Management and Innovation)
The purpose of this paper is to provide insight on the employability of recent Quantity Surveying graduates in the construction industry. The main aim is to establish employers’ perspective on the effect of higher education institution levels on the employability of these graduates. This can be achieved through understanding employers’ perception affecting QS graduates’ employability. Furthermore, the research will elaborate factors that affect QS graduate employability and how it can be improved. This research adopted a qualitative approach through interviewing graduate employers within Quantity Surveying firms. A total of ten interviews were carried out with the relevant subjects for the study and data was analyzed through identifying common trends among responses. The findings revealed that employers valued a combination of academic qualifications, practical skills, and soft attributes like communication and adaptability. Bridging the gap between university education and workplace demands through practical experiences was seen as crucial for enhancing graduate employability. The research is limited to Quantity Surveying graduates on the path to professional registration with SACQSP Council. Further studies on how university degrees are aligned to the performance of graduates in practical industry could be explored. This paper will be able to assist graduates in reflecting on their employability in the industry. This helps them to identify what employers require from graduates, therefore improving their career path.